Penerapan Aplikasi Google Meet Dalam Pembelajaran Matematika Di Kelas XI SMA Negeri 9 Samarinda Pada Masa Pandemi Covid-19 - Trisnawati (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
This study aims to obtain complete information about the application of the Google Meet application in mathematics learning for class XI at SMA Negeri 9 Samarinda during the Covid 19 pandemic. the learning process outside the classroom, but can be carried out anywhere and anytime. During the Covid -19 pandemic, this is the first time all educators in Indonesia have carried out an online learning process. As for learning mathematics in the era of the COVID-19 pandemic, which uses online mathematics learning. This type of research is descriptive quantitative, for a quantitative approach in the form of questionnaires and interviews from this approach, this study seeks to clearly describe what happened to the subject to analyze the application of the Google Meet application in mathematics learning in class XI at SMA Negeri 9 Samarinda during the Covid 19 pandemic. The research was students of class XI for the academic year 2020/2021 who were taken randomly so that a total of 120 students were obtained for filling out the questionnaire, and 36 students for the interview. This research was conducted at SMA Negeri 9 Samarinda. Based on student suggestions if online learning is better to use google meet because they can discuss directly with the teacher so that learning is more meaningful and easier to understand the material if it is carried out online.